Detention Of Suspects Under The Indonesian Criminal Law - Anzhari, Anzhari; Sunardi, Sunardi; Muhibbin, Moh. (International Journal of Law, Environment, and Natural Resources, 2023)
The research aims to describe the provisions of Indonesian criminal law regarding the detention of suspects and to analyze the legal protection of suspects during detention in terms of Indonesian criminal law. This research is a normative legal research, which examines laws and regulations in a coherent legal system and legal values ??related to the detention of suspects in the study of Indonesian criminal law. The results of the study show that the provisions for detaining suspects are regulated in Article 1 point 21 of the Criminal Procedure Code of Criminal Procedure. While in detention, suspects can exercise their rights in accordance with articles 50 to 68 of the Criminal Procedure Code (KUHAP).l protection is always associated with the concept of rechtstaat or the concept of the Rule of Law because the birth of these concepts cannot be separated from the desire to provide recognition and protection of human rights. A suspect has rights at the time of detention that are guaranteed by law, such as the right to receive and read a Detention Warrant or a Judge's Order which lists the identity of the suspect or defendant and states the reasons for the detention and a brief description of the crime case being suspected or charged and the place where he is being detained in accordance with Article 21 paragraph (2) Criminal Procedure Code.